Implementasi Fuzzy Tahani Dalam Memprediksi Restok Beras Di Toko Arta Kota Batu - Hakim, Lukman (JURNAL SISTEM KOMPUTER ASIA, 2024)
Toko Arta is a shop that provides household goods located in Batu City. One of the items available at Toko Arta is Mentari Rice, and it’s the best-selling commodity among the public. Sometimes this condition causes Toko Arta to have to provide or restock Mentari Rice in uncertain conditions, resulting in a less of Rice stock or a buildup in the warehouse due to relatively low demand. Therefore, the role of science is needed to help in solving this problem. One of the scientific disciplines that can be applied is fuzzy logic, and in this research, Tahani's fuzzy logic was implemented. The variables involved are initial stock, demand, supply and restock, with each set divided into three states, namely small, medium and large. Finally, the results of the research that the Mentari Rice stock in December 2023 will be 55.53 quintals. This result indicates an error of 15.6%, with an accuracy rate of 84.4%.